Injecting drug use in Brighton, Liverpool, and London: best estimates of prevalence and coverage of public health indicators. Issue 9 (13th August 2004) - Hickman, Matthew; Higgins, Vanessa; Hope, Vivian; Bellis, Mark; Tilling, Kate; Walker, Angeline; Henry, John
Abstract : Study objective: To estimate the prevalence of injecting drug use (IDU) in three cities in England and to measure the coverage of key public health indicators. Design: Capture-recapture techniques with covariate effects. Setting: Liverpool, Brighton, and 12 London boroughs, 2000/01. Participants: IDU collated and matched across five data sources—community recruited survey, specialist drug treatment, arrest referral, syringe exchange, and accident and emergency—896 in Brighton, 1224 in Liverpool, and 6111 in London. Main results: It is estimated that in 2000/01 the number and prevalence of IDU aged 15–44 was 2300 (95%CI 1500 to 3700) and 2.0% (95%CI% 1.3% to 3.2%) in Brighton; 2900 (95%CI 2500 to 5000) and 1.5% (95%CI 1.3% to 2.6%) in Liverpool; 16 700 (95%CI 13 800 to 21 600) and 1.2% (95%CI 1.0% to 1.6%) in 12 London boroughs; with a prevalence of 1.7% (95%CI 1.2% to 3.3%) in inner London. It is estimated that: less than one in four IDU are in treatment in the three areas; syringe exchange programmes covered about 25% of injections in Brighton and Liverpool and 20% in London; and that the annual opioid mortality rate among IDU was 2% in Brighton compared with less than 1% in Liverpool and London. Conclusions: Credible estimates of the prevalence of injecting drug use (and key public health indicators) can be determined using covariate capture-recapture techniques. These suggest that: targets to double the number in treatment are possible: syringe distribution should be increased; and further attention, especially in Brighton, given to reducing overdose mortality.